2007
DOI: 10.1097/01.phh.0000278027.56820.7e
|View full text |Cite
|
Sign up to set email alerts
|

Linking Accreditation and Public Health Outcomes

Abstract: Emerging public health standards, performance assessment tools, and accreditation models hold significant promise for defining and standardizing public health practice, yet the lack of empirical research on their relationship to outcomes represents a serious barrier to adoption. Given the growing interest and momentum related to public health agency assessment and accreditation efforts, there is increasing need for evidence that performance standards and associated accreditation programs are effective means fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 10 publications
0
29
0
Order By: Relevance
“…19 It has been suggested that conceptual models (logic models) could prove useful by providing a structure for exploring these complex relationships between public health practice and outcomes. 20 Logic models (also known as impact models) originate from the field of programme evaluation, and are typically diagrams or flow charts that convey relationships between contextual factors, inputs, processes and outcomes. 21 It is argued that logic models are valuable in providing a "roadmap" to illustrate influential relationships and components from inputs to outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 It has been suggested that conceptual models (logic models) could prove useful by providing a structure for exploring these complex relationships between public health practice and outcomes. 20 Logic models (also known as impact models) originate from the field of programme evaluation, and are typically diagrams or flow charts that convey relationships between contextual factors, inputs, processes and outcomes. 21 It is argued that logic models are valuable in providing a "roadmap" to illustrate influential relationships and components from inputs to outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…21 It is argued that logic models are valuable in providing a "roadmap" to illustrate influential relationships and components from inputs to outcomes. 20,22 These models have been used widely in the health promotion literature to identify domains underlying best practice. 23,24,25 The work outlined in this paper aimed to pilot a new approach to systematic review of the evidence, which had the potential to overcome these issues of study design hierarchies, limited available evidence, and complex causal pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Reviews of more than 90 years of effort to measure, describe, and improve public health practice and systems performance (82,94) show that many of the same basic challenges for measuring systems performance persist. In addition, new and re-emphasized priorities in public health practice, such as voluntary agency accreditation (46,58,72,91), workforce credentialing (12,16,23,68), quality improvement (74,75,85), and service value measurement (36,43,66), will increase expectations for PHSR science to integrate and understand effects of these efforts at multiple systems levels.…”
Section: Conclusion and Future Issuesmentioning
confidence: 99%
“…It was necessary, therefore, to develop a logic model specifically for this review. Originating from the field of programme evaluation, logic models (also known as theoretical, conceptual, or impact models) are typically diagrams or flow charts that illustrate pathways between inputs, strategies, outputs, and shortterm, intermediate and longer-term outcomes (Anderson et al, 2011;Joly et al, 2007). Designed to read from left to right, they provide a valuable road map that spells out how, and for whom, a programme is meant to produce the desired outcomes.…”
Section: Awareness Campaignsmentioning
confidence: 99%